Evaluation of cost effective approaches for nutrient removal in urban stormwater and wastewater: City of Fort Collins case study - Breidt, Sarah, author; Sharvelle, Sybil, advisor; Roesner, Larry, committee member; Goemans, Chris, committee member (Colorado State University. Libraries, 2015)
To respond to pending regulation that affects effluent nitrogen and phosphorus standards from urban watersheds, this study compares existing nutrient discharges from wastewater and stormwater sources in Fort Collins, Colorado and evaluates the benefits and costs of nutrient removal strategies identified in both sectors as a guide to urban planners. Six alternative wastewater advanced nutrient removal technologies were modeled in BioWin® to be integrated with the existing modified Bardenpho unit. Approximately 1,500 stormwater control measures (SCMs) are implemented in Fort Collins at present; however, not all provide water quality treatment. Two alternative stormwater scenarios were evaluated using the Simple Method and include: 1) retrofitting existing flood control SCMs to provide treatment, and 2) implementing SCMs to treat runoff from currently untreated impervious areas. Treatment level, environmental impacts, and 20-year lifecycle costs were determined for all alternatives and compared within a multi-criterion decision analysis (MCDA). Existing wastewater discharges of nitrogen and phosphorus are 2.0 and 1.5 times larger than those from stormwater, respectively. Removal efficiencies from these discharge nutrient levels were found to be between 7.5% and 30% for wastewater and 20% and 35% for stormwater. Although wastewater alternatives had large ranges of potential costs, all were determined to be more cost effective ($/lb. removal) than the stormwater scenarios. Struvite precipitation in all MCDA scenarios is the most advantageous alternative, followed by ammonia stripping and extended detention basin (EDB) retrofits.
Keywords: sidestream technologies; urban nutrient removal